You're invited [large type] - Jayatissa, Amanda (Wheeler Publishing, a part of Gale, a Cengage Company, 2022)
"When Amaya is invited to Kaavi's over-the-top wedding in Sri Lanka, she is surprised and a little hurt to hear from her former best friend after so many years of radio silence. But when Amaya learns that the groom is her very own ex-boyfriend, she is consumed by a single thought: She must stop the wedding from happening, no matter the cost. But as the week of wedding celebrations begin and rumors about Amaya's past begin to swirl, she can't help but feel like she also has a target on her back. When Kaavi goes missing and is presumed dead, all evidence points to Amaya. However, nothing is as it seems as Jayatissa expertly unravels that each wedding guest has their own dark secret and agenda, and Amaya may not be the only one with a plan to keep the bride from getting her happily ever after."--